2016
DOI: 10.1152/ajplung.00161.2016
|View full text |Cite
|
Sign up to set email alerts
|

14,15-Epoxyeicosatrienoic acid suppresses cigarette smoke condensate-induced inflammation in lung epithelial cells by inhibiting autophagy

Abstract: Epoxyeicosatrienoic acids (EETs) are metabolic products of free arachidonic acid, which are produced through cytochrome P-450 (CYP) epoxygenases. EETs have anti-inflammatory, antiapoptotic, and antioxidative activities. However, the effect of EETs on cigarette smoke-induced lung inflammation is not clear. Autophagy is believed to be involved in the pathogenesis of chronic obstructive pulmonary disease. In addition, nuclear erythroid-related factor 2 (Nrf2), a transcription factor that regulates many antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 43 publications
4
46
1
Order By: Relevance
“…These results indicated that cigarette smoke activated autophagy and induced the secretion of inflammatory cytokines in BEAS-2B cells and that the inhibition of autophagy inhibited the CSC-induced inflammatory response. In a previously published study by our group, we showed that in CSC-induced BEAS-2B cells, autophagy promoted secretion of the inflammatory cytokines, IL-6, IL-8, and MCP-1, by reducing p62 aggregation, which reduced translocation of Nrf2 into the nucleus, downregulating the expression of heme oxygenase-1 (HO-1), which can reduce the expression of inflammatory cytokines [29].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…These results indicated that cigarette smoke activated autophagy and induced the secretion of inflammatory cytokines in BEAS-2B cells and that the inhibition of autophagy inhibited the CSC-induced inflammatory response. In a previously published study by our group, we showed that in CSC-induced BEAS-2B cells, autophagy promoted secretion of the inflammatory cytokines, IL-6, IL-8, and MCP-1, by reducing p62 aggregation, which reduced translocation of Nrf2 into the nucleus, downregulating the expression of heme oxygenase-1 (HO-1), which can reduce the expression of inflammatory cytokines [29].…”
Section: Discussionmentioning
confidence: 94%
“…The procedure used to transfect and evaluate adenoviral mRFP-GFP-LC3 has been described previously [29]. Briefly, the day before transfection, good quality BEAS-2B cells were seeded into 24-well plates and cultured overnight.…”
Section: Transfection Assay and Adenoviral Tandem Fluorescent-tagged mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, these agents induce HO-1 expression, at least in part, by modulation of broad acting transcriptional repressors and transcription factors. More specifically, they involve post-translational downregulation of BACH1 and upregulation of NRF2 [275,291,297,298]. The latter is recognised as a key regulator of cellular defence against oxidative stress that is also strongly implicated in modulation of adipogenesis and adipose tissue remodelling [289,299,300].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that CoPP induces HO-1 by modulating the transcriptional repressors and transcription factors, the downregulation of BACH1 and upregulation of NRF2 [275,291,297,298].…”
Section: Ud-undeterminedmentioning
confidence: 99%